The Development of Thai Herbal Medicine During Rattanakosin Era (part 2) - Tankeyoon, Monthira; Tham-aree, Sopit (Journal of Basic and Applied Pharmacology, 2015)
Seven hundred and twenty four publications on the development of Thai herbal medicine during Rattanakosin Era were examined and analyzed. The results showed that 32.2 % of these publications were research reports, 50.4 % were theses, 16.6 % were articles, 0.8 % were the others. Nearly all of research reports and theses were experimental studies. These publications concerned with five hundred and twenty six varieties of medicinal plants in six branches of scientific study, but only twenty three plants have been studied more than one discipline. The pharmacological action of these plants has been tested on twenty four manifestations of disease, eight medicinal plants have been studied in human, and none of them, however, has been completely tested. There were very few studies of chronic toxicity of these medicinal plants. *Supported by the research grant of Chulalongkorn University